Teachers’ Strategies to Improve Students Self-Confidence in Speaking - Mira Ilya Maisaroh; Ari Prasetyaningrum; Hajriana Arfah (Departement of Mathematics Education, 2024)
This research aimed at find teachers’ strategies to improve students’ self-confidence in speaking. This study used qualitative descriptive method. Instrument of collecting data was interview, observation and questionnaire. The participant were sixth teachers and ten students of BestOne Education English Courses. Based on the findings, there was several strategies to improve students’ self-confidence. Those strategies are group discussion, increasing vocabulary, taking an approach by providing motivation and using technology as a learning media. These strategies were very helpful to encourage students’ self confidence in speaking, because each strategies giving a chance for students to practice speaking. Besides that, the advantages that students got from those, help students increase their vocabulary and build an interaction between passive and active students, and make the class more fun and not boring.